Identification and management of chronic kidney disease: A case study - Wijonarko Wijonarko; Ferry Ferry (Holistik Jurnal Kesehatan, 2024)
Background: Chronic kidney disease (CKD) is one of the most common chronic diseases affecting people in the world. CKD is a disorder of kidney function, namely the body's failure to maintain metabolism and fluid balance, so that it cannot recover due to the body being unable to maintain metabolism. Purpose: To identify appropriate bleeding in chronic kidney disease patients. Method: The design of this research is a case study in caring for clients with chronic kidney disease (CKD). The research object was two patients with a diagnosis at the Dr. H. Abdul Moeloek Regional General Hospital, Lampung Province. Maintenance care data collection is carried out by interviews, physical examination, and direct observation. Data analysis was carried out by evaluating treatment actions against the level of treatment achievement in patients. Results: Based on diagnosis, observation and physical examination, ineffective breathing patterns, hypervolemia, activity intolerance, disturbed sleep patterns and risk of nutritional deficit were found. Bleeding care for 3 x 24 hours shows that breathing patterns are becoming more normal, fluid intake is balanced, and physical activity is restored. Conclusion: Implementation of maintenance measures in CKD patients has an impact on improving breathing, balancing fluid intake, and physical activity conditions. Suggestion: There is a need to understand and the importance of nursing care, namely in carrying out priority actions for CKD patients.   Keywords: Chronic Kidney Disease (CKD); Identification; Management; Nursing Care.   Pendahuluan: Chronic kidney disease (CKD) menjadi salah satu penyakit kronis yang paling banyak menyerang masyarakat dunia. CKD merupakan gangguan fungsi ginjal yaitu tubuh gagal dalam mempertahankan metabolisme dan keseimbangan cairan, sehingga tidak dapat pulih kembali disebabkan oleh tubuh yang tidak mampu memelihara metabolisme. Tujuan: Untuk mengidentifikasi manajemen keperawatan yang sesuai pada pasien penyakit ginjal kronis. Metode: Desain penelitian ini adalah studi kasus dalam asuhan keperawatan pada klien chronic kidney disease (CKD). Objek penelitian sebanyak dua pasien dengan diagnosa di Rumah Sakit Umum Daerah Dr. H. Abdul Moeloek Provinsi Lampung. Pengumpulan data asuhan keperawatan dilakukan dengan wawancara, pemeriksaan fisik, dan observasi langsung. Analisa data dilakukan dengan melakukan evaluasi tindakan asuhan keperawatan terhadap tingkat pencapaian perawatan pada pasien. Hasil: Berdasarkan diagnosa, observasi, dan pemeriksaan fisik, didapatkan pola napas tidak efektif, hypervolemia, intoleransi aktivitas, gangguan pola tidur, dan resiko defisit nutrisi. Asuhan keperawatan selama 3x24 jam menunjukkan pola napas semakin normal, asupan cairan jadi seimbang, dan pulihnya aktivitas fisik. Simpulan: Pelaksanaan tindakan asuhan keperawatan pada pasien CKD memberikan pengaruh terhadap perbaikan pernapasan, keseimbangan asupan cairan, dan kondisi aktivitas fisik. Saran: Perlunya pemahaman dan pentingnya asuhan keperawatan yaitu dalam melakukan tindakan prioritas bagi pasien CKD.   Kata Kunci: Asuhan Keperawatan; Identifikasi; Penatalaksanaan; Penyakit Ginjal Kronis (PGK).